2013
DOI: 10.1007/s10096-013-1953-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous fungal peritonitis: a severe complication in patients with advanced liver cirrhosis

Abstract: Treatment of cirrhotic patients with spontaneous peritonitis using antibiotics occasionally fails. Fungal infections may be one of the causes of antibiotic treatment failure in such patients. In this study we evaluated the clinical significance and characteristics of spontaneous fungal peritonitis (SFP). Consecutive cirrhotic patients with spontaneous peritonitis treated between 2000 and 2005 at a tertiary care center in Seoul, Korea, were included. We analyzed the clinical characteristics and the prognosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
166
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(178 citation statements)
references
References 20 publications
7
166
4
1
Order By: Relevance
“…Spontaneous bacterial peritonitis is one of the most common infections in patients with cirrhosis. In a study of 416 patients with culture-positive spontaneous bacterial peritonitis there were 15 (3.5%) cases of fungal peritonitis [15]. The main species were Candida albicans and Cryptococcus neoformans.…”
Section: E4mentioning
confidence: 99%
“…Spontaneous bacterial peritonitis is one of the most common infections in patients with cirrhosis. In a study of 416 patients with culture-positive spontaneous bacterial peritonitis there were 15 (3.5%) cases of fungal peritonitis [15]. The main species were Candida albicans and Cryptococcus neoformans.…”
Section: E4mentioning
confidence: 99%
“…Patients with cirrhosis frequently either are exposed to fungal products (12) or develop fungal infections, with high mortality (13)(14)(15). Spontaneous fungal peritonitis is mainly caused by Candida species -in particular by Candida albicans in patients with cirrhosis (16).…”
Section: Introductionmentioning
confidence: 99%
“…5 Finally, our high (100%) mortality rate in fungal peritonitis/shock is consistent with other studies. 6 Prior studies have shown that directed anti-fungal therapy did not improve patient outcomes. 7 Hence, fungal peritonitis may potentially be a poor prognostic marker.…”
Section: Letters To the Editorsmentioning
confidence: 99%